2016
DOI: 10.1002/jnr.23708
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new low‐dose 6‐hydroxydopamine model of Parkinson's disease in rat

Abstract: Intrastriatal administration of 6-hydroxydopamine (6-OHDA) induces partial degeneration of the nigrostriatal pathway, mimicking the pathology of Parkinson's disease (PD). Setting up the partial lesion model can be challenging because a number of experimental settings can be altered. This study compares seven experimental settings in a single study on d-amphetamine-induced rotations, tyrosine hydroxylase (TH)-positive neurites in the striatum, dopamine transporter (DAT)-positive neurites in the striatum, and TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 46 publications
5
40
0
Order By: Relevance
“…The intrastriatal injection of 6-OHDA causes a progressive retrograde and dose-dependent neuronal degeneration in the nigrostriatal pathway [13, 14]. The degree of lesion can be intensified if 6-OHDA is injected into different striatal sites [15]. In the present study, the animals were anesthetized with the association of xylazine (10 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…The intrastriatal injection of 6-OHDA causes a progressive retrograde and dose-dependent neuronal degeneration in the nigrostriatal pathway [13, 14]. The degree of lesion can be intensified if 6-OHDA is injected into different striatal sites [15]. In the present study, the animals were anesthetized with the association of xylazine (10 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Stereology, however, is timeconsuming and often requires a specialized microscope and software for efficient and unbiased counting. New computational methods have enhanced counting, e.g., implementing MatLab in calculations provide similar results as obtained with the optical fractionator unbiased counting (Penttinen et al, 2016). However, this still requires manual labor, and newer methods aim to automatize counting.…”
Section: Quantification Of Dopaminergic Neurites and Cell Bodiesmentioning
confidence: 98%
“…These parameters have since been further optimized by others for further stability (Heuer, Smith, Lelos, Lane, & Dunnett, 2012;Penttinen et al, 2016). Comparing various dosing regimens, needles, and injection sites, we have found that the most reliable partial lesion and behavioral effect, analyzed by TH staining and drug-induced rotations, was obtained by injecting 3 × 2 μg of 6-OHDA into three regions of the striatum of rats (Penttinen et al, 2016). This low-dose model produces consistent lesions, and therefore, reduces the number of animals needed for experiments.…”
Section: Of 33mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we first counted the number of astrocytes by FindMyCell, Ilastik, custom thresholdbased script 20 and ImageJ in randomly selected sections from the brains of control and morphine-treated animals described by Jokinen 26 . Thus, we compared the performance of FindMyCells to semi-automated tools based on both machine-learning principles and manual thresholding.…”
Section: Introductionmentioning
confidence: 99%